P-C12 Hepatic and peripheral immunophenotypic and functional differences of CCR5+ and CCR5- T-cells in HIV/HCV coinfected and HCV monoinfected patients. (March 2017) - Tang, Lydia; Ward, Haley; Poonia, Bhawna; Kottilil, Shyam; Shrivistava, Shikha
Abstract : Liver fibrosis is accelerated in HIV/HCV coinfection. CC chemokine receptor 5 (CCR5) is expressed on T-cells and plays a role in migration and activation of cells. A profibrogenic role has been described in the pathogenesis of cirrhosis. Aim: Determine effect of HIV coinfection on CCR5+ T-cell function and migration. Method: Paired peripheral blood mononuclear cells and liver infiltrating lymphocytes from 21 HIV/HCV and 14 HCV subjects were analyzed for CD4 and CD8 T-cell CCR5 expression by flow cytometry. PBMCs from 5 HIV/HCV and 5 HCV subjects were flow sorted for CCR5+ and CCR5- T-cells. Phenotypic and functional characterization by 12-color flow cytometric analysis was conducted pre and post-stimulation with HCV genotype specific overlapping pooled peptides. Statistical Analysis: t-test, significance at p<0.05. Results: Hepatic CD4 and 8 CCR5+ T-cell populations were higher than peripheral in both HIV/HCV and HCV subjects (p < 0.0001) and higher in HIV/HCV compared to HCV (p<0.0001). Contrastingly, peripheral CD4+CCR5+ populations were smaller in HIV/HCV compared to HCV (p=0.006), but expressed more CXCR3 than HIV/HCV CD4+CCR5− (p=0.04) and HCV CD4+CCR5+ T-cells (p=0.05). Furthermore, in HIV/HCV, CD4+CCR5+ T-cells expressed more activation (HLADR+CD38+) and exhaustion (PD-1) markers (both p=0.04), and produced less IFN-gamma in response to HCV peptide stimulation (p=0.05) than CD4+CCR5+ T-cells from HCV subjects. CD8+CCR5+ T-cells from HIV/HCV subjects also expressed higher exhaustion markers Tim-3 and CTLA-4 (p=0.02 and 0.04) than HCV subjects. Conclusions: Our results suggest that in HIV/HCV coinfection, activated CD4+CCR5+CXCR3+ T-cells migrate to the liver. These cells are not HCV specific and may lead to non-specific inflammation and accelerated fibrogenesis in HIV/HCV coinfected patients. Strategies to block CCR5 could be used as a therapeutic tool for fibrosis progression.